Upaya Surat Kabar Harian Umum Haluan Padang Dalam Mempertahakan Eksistensi Di Era Media Online - Rahmatullah, Ikh'wan; Flowerina, Indria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The rapid development of information and communication technology has caused a shift in information consumption patterns in society which has resulted in competition in the media industry, one of which is print media, where currently print media not only competes with other print media, but also competes with online media which is much interactive and interactive. efficient. Many newspapers have gone out of business because they failed to maintain their existence amidst the rapid growth of online media. This research aims to determine the efforts made by the Haluan Padang General Daily Newspaper in maintaining its existence in the online media era as one of the oldest conventional media in West Sumatra. This research is descriptive qualitative research which produces descriptive data in the form of writing or speech, as well as the behavior of people being observed. This method is applied to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually and in groups. To describe this research using the media convergence theory put forward by Henry Jenkins (2006) in his book entitled "Convergence Culture: Where Old and New Media Collide" there are 3 elements of convergence, namely Computing (data on computers), Communication (communication), and Content ( content material) and Adaptation Me theory. The Haluan Padang General Daily Newspaper has made efforts to maintain its existence by carrying out computer/technology convergence, business convergence, content convergence as well as promotional or personal branding efforts. Through these efforts, Haluan Padang Daily remains relevant and competitive in an increasingly competitive media market. Despite facing various challenges, dedication to providing quality information and strong involvement with the community is the key for print media such as Harian Haluan Padang to continue to survive and face challenges in the future or what is known as the Cultivation Adaptation Theory by George Gerbner in the 1960s as supporting theory.